Censing in the traditional culture of old believers-bespopovtsy of Ust-Tsilma - Dronova T.I. (Вестник археологии, антропологии и этнографии)
In this article, censing in the folk culture of Russian old believers-bespopovtsy living in the Ust-Tsilemsky District of the Komi Republic has been analyzed. In the post-schism period, the church rite of censing was inherited by lay old believers, adapted to their religious culture, and at present time it is actively practiced by them. The article provides a dialect vocabulary reflecting the process of censing and identifies the circle of lay people who have the right to perform this ritual. In the process of research, it has been established that in the religious life of the Ust-Tsilma old believers, censing frankincense is the most important ritual action, reuniting a person with God, having a purifying and apotropaic meaning, and establishing a connection between the living and the dead. It is also an important element in the routine ritual life of the Ust-Tsilma old believers, having its own local characteristics: it is performed not only during the church services, but also in everyday life. Censing is performed in private homes on holy days, on purchased equipment, and livestock. This ritual is given a particular importance in funeral and memorial rites. Each action is accompanied by censing and is aimed at purifying the deceased in the process of preparing them for their final journey: the moment of death of a person, ablution, transfer of the body into the coffin, clearing the road to the cemetery. Censing constitutes an obligatory part of funeral rites.